A dual-functional metal phosphate for high proton conduction and selective luminescence turn-on sensing of Co2+ ions. Issue 11 (20th February 2020) - Zhou, Shu-Fang; Wu, Guo-Mei; Lin, Tian; Zhang, Chen-Xi; Wang, Qing-Lun
Abstract : The [Zn(H2 PIPZ)](H2 O) n (compound 1 ) detects Co 2+ ions with turn on fluorescent and proton conductivity of composite membrane 1@PVA10 is ten times higher than compound 1 at 98% RH and 353 K. Abstract : In this work, [Zn(H2 PIPZ)](H2 O) n was synthesized by self-assembly of an N, N ′-piperazinebis(methylenephosphonic acid) [H4 PIPZ] ligand and zinc chloride under hydrothermal conditions. The Zn 2+ ion is four-coordinated by oxygen atoms from four different H2 PIPZ 2− ligands to form a tetrahedral configuration. The Zn 2+ tetrahedral units are further connected by a phosphate group of the H2 PIPZ 2− ligand to form a 3D structure. AC analysis shows that the proton conductivity of compound 1 is excellent and by introducing 1 into PVA to make composite membranes, the proton conductivity of composite membrane 1 @PVA-10 (10% wt) reached 2.78 × 10 −4 S cm −1 at 98% RH and 353 K, which is approximately ten times higher than that of 1 . In addition, compound 1 has excellent selectivity and sensitivity to cobalt ions in water due to turn on fluorescence. The detection limit is 1.0 × 10 −8 M. In contrast, the Fe 3+ ion has a turn off fluorescence effect on 1 and the detection limit is 1.0 × 10 −6 M.